Rubber Dam: Is it a Popular Method of Field Isolation among Dentists in Karachi? - Asaad Javaid Mirza; Maaz Asad Javaid; Shama Asghar (KARACHI MEDICAL AND DENTAL COLLEGE, 2017)
Objective: To find out the frequency of rubber dam usage among clinical students, interns and dental practitioners and the barriers they come across to place it routinely in their practices. Methods: An observational cross-sectional study was performed from October 2016  to  January  2017 using non-probability convenience sampling. A questionnaire was meticulously designed based on questionnaires used in similar studies in the  past.  The  target  population  in  this  study  was  clinical  dental students, interns and the faculty  members  working  in  various  teaching  institutions  in  Karachi  and involved in  general  dental  practice.  Data  from  completed  questionnaire  was  analysed  using  SPSS version 20. Results: With the healthy response rate of 81%, this study shows that the majority (76%) of clinical students, interns and practicing dentists in Karachi, Pakistan continue to  ignore  the  rubber  dam  placement in their routine practices. Total 89% of non-users did not use  it  as  they  find  it  time  con- suming and 66% of them mentioned that  it  is  difficult  to  place.  Couple  of  other  reasons  for  which  more than 50% of respondents  avoid  using  rubber  dam  are  frequent  tearing  of  the  sheet  and patient's fear or abhorring attitude towards placement of rubber dam. Conclusion: This study suggests that use of rubber dam is an unpopular method for isolation of op-  erative site among clinical students, interns and clinicians working in Karachi.